mathematical induction
play

mathematical induction Sept. 29, 2017 1 For all 1 , 1 + 2 + 3 + - PowerPoint PPT Presentation

COMP 250 Lecture 10 mathematical induction Sept. 29, 2017 1 For all 1 , 1 + 2 + 3 + . + 1 + = ( + 1) 2 How to prove such a statement ? By proof, we mean a formal logical argument that convincely


  1. COMP 250 Lecture 10 mathematical induction Sept. 29, 2017 1

  2. For all π‘œ β‰₯ 1 , 1 + 2 + 3 + … . + π‘œ βˆ’ 1 + π‘œ = π‘œ(π‘œ + 1) 2 How to prove such a statement ? By β€œproof”, we mean a formal logical argument that convincely shows the statement is true. Note that β€œ convincely ” is itself not well defined. 2

  3. 1 + 2 + … + π‘œ βˆ’ 1 + π‘œ Rewrite by considering π‘œ/2 pairs : 1 + 2 + β‹― + π‘œ 2 + ( π‘œ 2 + 1) … + π‘œ βˆ’ 1 + π‘œ If π‘œ is even, then adding up the π‘œ/2 pairs gives π‘œ/2 *( π‘œ + 1). What if π‘œ is odd? 3

  4. What if π‘œ is odd? Then, π‘œ -1 is even. So, 1 + 2 + … + π‘œ βˆ’ 1 + π‘œ π‘œβˆ’1 ( 2 βˆ— π‘œ ) + π‘œ = π‘œβˆ’1 = ( 2 + 1) βˆ— π‘œ = π‘œ+1 2 βˆ— π‘œ which is the same formula as before. 4

  5. Mathematical Induction Consider a statement of the form: β€œFor all π‘œ β‰₯ π‘œ 0 , 𝑄 π‘œ is true” where π‘œ 0 is some constant and proposition 𝑄(π‘œ) has value true or false for each π‘œ . Mathematical induction is a general technique for proving such a statement. 5

  6. β€œ For all π‘œ β‰₯ π‘œ 0 , 𝑄 π‘œ is true” For all π‘œ β‰₯ 1 , π‘œ(π‘œ+1) 1 + 2 + … + π‘œ βˆ’ 1 + π‘œ = 2 6

  7. Mathematical induction requires proving two things: Base case: β€œP( π‘œ 0 ) is true.” Induction step: β€œFor any 𝑙 β‰₯ π‘œ 0 , if P(𝑙) is true, then P(𝑙 + 1) is also true.” 7

  8. 1 2 π‘œ 0 k k+1 Base case: β€œP( π‘œ 0 ) is true .” Induction step: β€œFor any k β‰₯ π‘œ 0 , if P(k) is true , then P(k+1) is also true.” The statement β€œP(k) is true” is called the β€œinduction hypothesis”. 8

  9. Base case: Induction step: For any k >= π‘œ 0 , if P(k) is true P( π‘œ 0 ) is true. then P(k+1) is true. 1 2 n0 k k+1 Thus we have proved: For any n >= π‘œ 0 , P(n) is true. 1 2 n0 k k+1

  10. For all π‘œ β‰₯ 1 , Statement: 1 + 2 + 3 + … . + π‘œ βˆ’ 1 + π‘œ = π‘œ(π‘œ + 1) 2 Proof (base case, n=1): 10

  11. For all π‘œ β‰₯ 1 , Statement: 1 + 2 + 3 + … . + π‘œ βˆ’ 1 + π‘œ = π‘œ(π‘œ + 1) 2 Proof (base case, n=1): 1(1+1) 1 = (true) 2 11

  12. induction hypothesis is that P(𝑙) is true: 1 + 2 + … + 𝑙 = 𝑙(𝑙 + 1) 2 Base case: Induction step: For any k >= π‘œ 0 , if P(k) is true P( 1 ) is true. then P(k+1) is true. 1 2 k k+1

  13. Proof of Induction Step: ( 1 + 2 + 3 + … . + 𝑙) + 𝑙 + 1 by induction hypothesis 𝑙(𝑙+1) + 𝑙 + 1 = 2 = 13

  14. Proof of Induction Step: ( 1 + 2 + 3 + … . + 𝑙) + 𝑙 + 1 by induction hypothesis 𝑙(𝑙+1) + 𝑙 + 1 = 2 𝑙 2 + 1) (𝑙 + 1) = ( 1 2 ( 𝑙 + 2 ) (𝑙 + 1) = Thus, 𝑄 𝑙 𝑗𝑑 𝑒𝑠𝑣𝑓 π‘—π‘›π‘žπ‘šπ‘—π‘“π‘‘ 𝑄 𝑙 + 1 𝑗𝑑 𝑒𝑠𝑣𝑓. 14

  15. Possible confusion 𝑄 𝑙 has value true or false (Boolean). So, 𝑄 𝑙 𝑗𝑑 𝑒𝑠𝑣𝑓 means what? 15

  16. Examples β€œ 3 = 2 + 1 ” is true. β€œ 3 = 2 + 2 ” is false. 16

  17. Examples β€œ 3 = 2 + 1 ” is true. β€œ 3 = 2 + 2 ” is false. β€œIf 3 = 2 + 2 then 5 > 7” is true. If this is a mystery to you, then I strongly advise you to take MATH 240 or MATH 318 (logic). 17

  18. Mathematical Induction: Example 2 Prove the following statement: For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . 2 π‘œ 2π‘œ + 1 π‘œ 0 1 2 3 4 18

  19. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Note: P( π‘œ ) is false for n= 1, 2. But that has nothing to do with what we need to prove. Proof (base case, π‘œ =3): 19

  20. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Note: P( π‘œ ) is false for n= 1, 2. But that has nothing to do with what we need to prove. Proof (base case, π‘œ =3): 2*3 + 1 < 8 (true) 20

  21. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 21

  22. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 𝑙 + 1 + 1 = ? 2𝑙 + 2 + 1 (This is 2π‘œ + 1 where π‘œ = 𝑙 + 1 .) 22

  23. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 𝑙 + 1 + 1 = 2𝑙 + 2 + 1 by induction hypothesis < 2 𝑙 + 2 23

  24. For all π‘œ β‰₯ 3 , 2π‘œ + 1 < 2 π‘œ . Statement: Proof of Induction Step: We want to show that P(k) implies P(k+1). 2 𝑙 + 1 + 1 = 2𝑙 + 2 + 1 by induction hypothesis < 2 𝑙 + 2 < 2 𝑙 + 2 𝑙 , for k β‰₯ 3 This inequality is also true for k >=2 but we don’t care because we are trying to = 2 𝑙+1 prove for k>=3. 24

  25. Base case: Induction step: For any k >= π‘œ 0 , if P(k) then P(k+1). P( π‘œ 0 ) is true. 1 2 n0 k k+1 Thus, For any n >= π‘œ 0 , P(n) is true. 1 2 n0 k k+1

  26. Example 3 Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . 2 π‘œ π‘œ 2 π‘œ 0 1 2 3 4 5 26

  27. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): Induction step: 27

  28. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): 25 < 32 Induction step: What do we assume ? What do we want to prove ? 28

  29. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): 25 < 32 Induction step: What do we assume ? 𝑙 2 < 2 𝑙 , 𝑙 β‰₯ 5 What do we want to show ? (𝑙 + 1) 2 < 2 𝑙+1 29

  30. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): 25 < 32 Induction step: (𝑙 + 1) 2 = 𝑙 2 + 2𝑙 + 1 30

  31. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): 25 < 32 Induction step: (𝑙 + 1) 2 = 𝑙 2 + 2𝑙 + 1 by induction hypothesis < 2 𝑙 + 2𝑙 + 1 31

  32. Statement: For all π‘œ β‰₯ 5 , π‘œ 2 < 2 π‘œ . Base case (n = 5): 25 < 32 Induction step: (𝑙 + 1) 2 = 𝑙 2 + 2𝑙 + 1 by induction hypothesis < 2 𝑙 + 2𝑙 + 1 by Example 2 < 2 𝑙 + 2 𝑙 = 2 𝑙+1 32

  33. Example 4 : Fibonacci Sequence 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, …. 𝐺 0 = 0 𝐺 1 = 1 𝐺 π‘œ + 2 = 𝐺 π‘œ + 1 + 𝐺(π‘œ) , for π‘œ β‰₯ 0. Statement: For all π‘œ β‰₯ 0, 𝐺 π‘œ < 2 π‘œ 33

  34. 𝐺 0 = 0 𝐺 1 = 1 𝐺 π‘œ + 2 = 𝐺 π‘œ + 1 + 𝐺(π‘œ) , for π‘œ β‰₯ 0. Base case(s): π‘œ = 0: 0 < 2 0 is true. π‘œ = 1: 1 < 2 1 is true. 34

  35. 𝐺 0 = 0 𝐺 1 = 1 𝐺 π‘œ + 2 = 𝐺 π‘œ + 1 + 𝐺(π‘œ) , for π‘œ β‰₯ 0. Induction step: 𝐺 𝑙 + 1 = 𝐺 𝑙 + 𝐺 𝑙 βˆ’ 1 by induction hypothesis < 2 𝑙 + 2 π‘™βˆ’1 35

  36. 𝐺 0 = 0 𝐺 1 = 1 𝐺 π‘œ + 2 = 𝐺 π‘œ + 1 + 𝐺(π‘œ) , for π‘œ β‰₯ 0. Induction step: 𝐺 𝑙 + 1 = 𝐺 𝑙 + 𝐺 𝑙 βˆ’ 1 by induction hypothesis < 2 𝑙 + 2 π‘™βˆ’1 < 2 𝑙 + 2 𝑙 = 2 𝑙+1 36

Download Presentation
Download Policy: The content available on the website is offered to you 'AS IS' for your personal information and use only. It cannot be commercialized, licensed, or distributed on other websites without prior consent from the author. To download a presentation, simply click this link. If you encounter any difficulties during the download process, it's possible that the publisher has removed the file from their server.

Recommend


More recommend